Osteocalcin as a negative regulator of serum leptin concentration in humans: insight from triathlon competitions - Guadalupe-Grau, A.; Ara, I.; Dorado, C.; Vicente-Rodriguez, G.; Perez-Gomez, J.; Cabrero, J. C.; Serrano-Sanchez, J. A.; Santana, A.; Calbet, J. A. L. (European Journal of Applied Physiology, 2010)
Osteocalcin is a hormone produced by osteoblasts which acts as a negative regulator of fat mass, protecting against diet induced obesity and insulin resistance in rodents. To determine if an acute increase in osteocalcin concentration is associated with opposed changes in circulating leptin levels and insulin resistance we studied 15 middle and long distance male triathletes, (age 32.1 ± 6.9 years), before and 48 h after an Olympic (OT) or an Ironman (IT) triathlon competition. Muscle power, anaerobic capacity, body composition (dual-energy X-ray absorptiometry), and serum concentrations of testosterone, dihydrotestosterone, osteocalcin, leptin, glucose, insulin and insulin resistance (HOMA) were determined pre- and post-race. Pre- and 48 h post-race total and regional lean body mass was not altered, but fat mass was similarly increased (~250 g) 48 h after the competitions. This elicited an increase in plasma leptin of 33% after the IT while it remained unchanged after the OT, likely due to a 25% increase in plasma osteocalcin which occurred only after the OT (all p < 0.05). Post-race HOMA remained unchanged in OT and IT. Performance was normalized 48 h after the competitions, with the exception of a slightly lower jumping capacity after the IT. Serum testosterone concentration tended to decrease by 10% after the IT whilst dihydrotestosterone was reduced by 24% after the IT. In conclusion, an acute increase in serum osteocalcin concentration blunts the expected increase of serum leptin concentration that should occur with fat mass gain. This study provides evidence for osteocalcin as a negative regulator of serum leptin in humans.